2015
DOI: 10.1177/2151458514565663
|View full text |Cite
|
Sign up to set email alerts
|

Orthopedic Trauma and Aging

Abstract: The elderly (age 70þ) patient with orthopedic trauma is a rapidly growing subset of patients in the United States. Due to increased medical comorbidities and decreased physiological reserve, morbidity and mortality after trauma may significantly differ from those patients younger than 70 years old. A retrospective review was performed to investigate the effect of age on orthopedic trauma. A total of 870 records of patients with orthopedic trauma from 2006 to 2009 at our Level One trauma center were reviewed. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 12 publications
(14 reference statements)
1
12
0
Order By: Relevance
“…Such laboratories have the unique opportunity to use surgical waste materials, occurring during TKA. Since TKA is a very common surgery (considering the present demographics, the incidence will only increase (Peterson et al, 2015)), this approach could make cartilage-related studies far more available also for laboratories with limited resources, and hence push the overall development of this field towards novel and cheaper therapeutic solutions. Based on our results, we can claim that the combination of the use of surgical waste tissue occurring during TKA, and analysis by inverted optical microscopy and chondrocyte specific gene expression, as well confirmation of chondrocyte specific production, indeed results in an alternative and affordable means to boost cartilage-related research in the  future.…”
Section: Discussionmentioning
confidence: 99%
“…Such laboratories have the unique opportunity to use surgical waste materials, occurring during TKA. Since TKA is a very common surgery (considering the present demographics, the incidence will only increase (Peterson et al, 2015)), this approach could make cartilage-related studies far more available also for laboratories with limited resources, and hence push the overall development of this field towards novel and cheaper therapeutic solutions. Based on our results, we can claim that the combination of the use of surgical waste tissue occurring during TKA, and analysis by inverted optical microscopy and chondrocyte specific gene expression, as well confirmation of chondrocyte specific production, indeed results in an alternative and affordable means to boost cartilage-related research in the  future.…”
Section: Discussionmentioning
confidence: 99%
“…Since trauma is a disease process that affects all age groups, elderly make up one of the fastest growing segments. Furthermore, mortality and morbidity are influenced by age, physical condition, and comorbidities and, therefore, elderly might be triaged to a higher level trauma center more quickly than their younger equivalents [15, 16]. The 13 % increase in P-HEMS presence in the prehospital phase is most likely due to the fact that in 2009, the Dutch government granted 24/7 coverage for the four Dutch P-HEMS crews, allowing them to also do night flights [17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, another study examining patients admitted for orthopedic trauma demonstrated no significant difference in hospital length of stay in the younger age group compared to patients 70 years and older; however, those patients 70 years and older had a significantly longer ICU stay than the younger age group [14].…”
Section: Discussionmentioning
confidence: 88%
“…Another study completed by Taylor et al demonstrated that patients ≥65 years of age who had experienced blunt trauma had significantly longer hospital stays and higher mortality rates than younger trauma patients [ 13 ]. On the contrary, another study examining patients admitted for orthopedic trauma demonstrated no significant difference in hospital length of stay in the younger age group compared to patients 70 years and older; however, those patients 70 years and older had a significantly longer ICU stay than the younger age group [ 14 ].…”
Section: Discussionmentioning
confidence: 99%